The Architectural Heritage of Baghdad in Ibn Al-Faqih Hamadani's Book Baghdad the City of Peace And its impact on Sustainable Development (Journal of the College of Education for Women, 2019)
This research shows the importance of Baghdad in the field of urban heritage and was demonstrated in the Ibn al-Fiqh al-Hamdani's book Baghdad the City of Peace in which he focused on many urban aspects and reviewing its historical importance by connecting them with modern events and the role they play in cultural and civilized construction which included: mosques, schools and markets etc. and the service providing institutions and other pillars of the Islamic cities through showing the development back then and its importance as an integral part of the urban and cultural heritage of the Islamic cities in general and Baghdad city in particular. In his book Baghdad the City of Peace, Ibn al-Faqih Hamadhaani carried plenty of data about Baghdad, in relevance to urban, civilized and intellectual life which included: feudalism, skylight and city gates, and other service centers that were abundant in the city, which formed in its content a part of the curriculum that was followed by him as the base he used as sporadic categories which had an effect in achieving sustainable development and building cultural bridges between nations in the intellectual field and to observe the development which the pillars mentioned in the book witnessed as these pillars represent an important link of the knowledge, communication and cultural formation links, these links are considered with benefits over the ages. This is one of the goals through which Ibn al-Fiqh al-Hamdani expressed the depth of that heritage, including its exploits and personalities.